ChemInform Abstract: Tsuji—Wacker Oxidation of Terminal Olefins Using a Palladium—Carbon Nanotube Nanohybrid. Issue 49 (December 2015) - Donck, Simon; Gravel, Edmond; Shah, Nimesh; Jawale, Dhanaji V.; Doris, Eric; Namboothiri, Irishi N. N.
Abstract: Methyl ketones are prepared by selective oxidation of terminal olefins using palladium‐based nanohybrids in combination with cupric chloride as co‐catalytic system.